Application of Hero's Journey and Archetype Functions in Films - Reza Noormansyah; Budi Dwi Arifianto (Jogjakarta Communication Conference (JCC), 2023)
Researchers tried to make the film Vengeance Is Mine, All Others Pay Cash For Using Chirstopher Vogler's heros journey, this theory presents twelve heroic journeys from the protagonist to become more individual than ever. In this study, there are interesting findings such as the stages of the hero's journey that can be found in this film are not sequential, indeed it only occurs in meetings with the mentor, where it occurs when Ajo is at the stage of the ordeal and also the resurrection. Meeting with the mentor occurred several times, namely when meeting Jelita and Ki Jempes. There is a shift in the protagonist, when Ajo is in prison Ajo is weakened as the protagonist and then the protagonist shifts to Iteung who will avenge Ajo. Archetype on Ggembul's uncle who has three masks namely; Herald, Threshold and Trickster.